Experimentation works : the surprising power of business experiments - Thomke, Stefan H. (Boston, Massachusetts : Harvard Business Review Press, 2020)
"When it comes to innovation, relying on intuition won't cut it anymore. Whether it's improving customer experiences, trying out new business models, or developing new products, even the most experienced managers often get it wrong. This is especially true in the online world, where predicting customer behavior is virtually impossible. Managers can, however, discover whether a new product, service, or business model will fail or succeed--by subjecting it to rigorous experimentation. Think about it. A pharmaceutical company would never introduce a new drug without first conducting a round of experiments based on established scientific protocols. Yet that's essentially what many companies do when they roll out new products and services. As Harvard Business School professor Stefan Thomke shows in this eye-opening and essential book, the "best guess" approach to innovation is changing fast. There are now leading companies that conduct more than ten thousand online controlled experiments annually, engaging millions of users. These organizations have discovered that an "experiment with everything" approach has a big payoff, giving them a considerable competitive advantage. How can you do this at your company? Leaders and managers need to create an "experimentation organization" that masters the science of testing and puts the discipline of experimentation at the center of the innovation process. It used to take companies years to build the infrastructure and develop the expertise to run hundreds of experiments each day. But Thomke shows how, with advances in technology, these capabilities are at the fingertips of almost any business professional. By combining the power of software and the rigor of controlled experiments, today's managers can make better decisions, create better customer experiences, and generate huge financial returns. Filled with engaging and instructive stories of leading experimentation organizations, Experimentation Works will be your guidebook to
Preface. A tribute to the scientific method: why I wrote the book (and why you should read it). Understanding the power of thinking and acting scientifically. Entering a new age of large-scale business experimentation -- Introduction. The business experimentation imperative: the need for business experiments to drive innovation and profitable growth. Deploying large-scale experimentation as a business-wide practice. Brief introduction to the book's ideas and frameworks -- Why experimentation works: the role of business experimentation in innovation. Understanding the power of tools and the experimentation process. Leveraging the operational drivers of high-velocity learning -- What makes a good business experiment?: the elements of a good business experiment. Seven questions that yield better management decisions. Appreciating the limits of experimentation -- How to experiment online: the business value of A/B testing. Leveraging the power of incremental innovation for business performance. Learning the best experimentation practices from leading digital companies -- Can your culture handle large-scale experimentation?: the seven attributes of a true experimentation culture. Diagnosing and addressing cultural obstacles. Adopting a new management model for experimentation organizations -- Inside an experimentation organization: the operating model of a true experimentation organization. Democratizing testing through process, management, and cultural discipline. Using technology, scale and velocity for competitive advantage -- Becoming an experimentation organization: the steps to becoming a true experimentation organization. Using the 7S's and ABCDE frameworks to analyze your situation. Deploying experimentation tools most effectively -- Seven myths of business experimentation: the myths that undermine experimentation and innovation. Realizing that your actions will lead to opposite reactions. Addressing fallacies that slow down progress -- Epilogue. A brief look
Includes bibliographical references and index.
Online resource: title from PDF title page (OverDrive, viewed February 21, 2020)
Added to collection customer.56279.3
Keywords: Business -- Technological innovations; Marketing research; Creative ability in business; Consumers -- Research; Success in business; elektronické knihy; electronic books